Influence of Technological Digitalization on Moral Degradation among Adolescents - Afni, Nur (Journal of Education Method and Learning Strategy, 2023)
This study aims to focus on the analysis of teaching behavior, attitudes, obligations, etiquette and morals that are generally recognized as good and bad. Meanwhile, morals itself refers to manners, including all aspects of etiquette and traditional behavior. This research is qualitative with descriptive analysis techniques with library research where this research seeks to describe existing phenomena that are taking place currently . The decline in the moral level of teenagers in Indonesia is a complex problem and requires in-depth understanding from various points of view. Therefore, it is necessary to explore this problem from a Muslim's perspective , to find a solution to the problem, especially from a modern Islamic perspective. As the majority religion in Indonesia, Islam has great potential in providing solutions to overcome the problem of juvenile delinquency. Apart from that, in the context of increasingly rapid globalization and modernization, modern Islam can provide a view that is in line with current developments and technology. Therefore, this research aims to explain the moral degradation of teenagers in the 5.0 era from a modern Islamic perspective, with the hope of providing the right solution to the problems raised.